2020
DOI: 10.1021/acsami.0c03696
|View full text |Cite
|
Sign up to set email alerts
|

Determining Factor on the Polarization Behavior of Magnesium Deposition for Magnesium Battery Anode

Abstract: To clarify the origin of the polarization of magnesium deposition/dissolution reactions, we combined electrochemical measurement, operando soft X-ray absorption spectroscopy (operando SXAS), Raman, and density functional theory (DFT) techniques to three different electrolytes: magnesium bis­(trifluoromethanesulfonyl)­amide (Mg­(TFSA)2)/triglyme, magnesium borohydride (Mg­(BH4)2)/tetrahydrofuran (THF), and Mg­(TFSA)2/2-methyltetrahydrofuran (2-MeTHF). Cyclic voltammetry revealed that magnesium deposition/dissol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
80
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(83 citation statements)
references
References 56 publications
2
80
1
Order By: Relevance
“…[18,28,68] Similar findings were recently described by Tuerxun et al for MgTFSI 2 in different organic solvents (THF, diglyme), based on the comparison of the calculated HOMO/ LUMO energy levels of the free TFSI À and of the MgTFSI 2 cluster, respectively. [20] In this case, implicit solvation effects were included, while explicit solvent effects by coordination of solvent molecules were not considered. Furthermore, we found that the addition of one BMP-TFSI ion pair slightly reduces the electron affinity E A .…”
Section: Simulationmentioning
confidence: 99%
See 1 more Smart Citation
“…[18,28,68] Similar findings were recently described by Tuerxun et al for MgTFSI 2 in different organic solvents (THF, diglyme), based on the comparison of the calculated HOMO/ LUMO energy levels of the free TFSI À and of the MgTFSI 2 cluster, respectively. [20] In this case, implicit solvation effects were included, while explicit solvent effects by coordination of solvent molecules were not considered. Furthermore, we found that the addition of one BMP-TFSI ion pair slightly reduces the electron affinity E A .…”
Section: Simulationmentioning
confidence: 99%
“…[12] In general, most investigations so far have focused on salt/solvent combinations that allow reversible Mg deposition/dissolution without the formation of a protective surface layer. Among those, a limited number of electrolytes consisting of commercially available magnesium salts such as Mg(BH 4 ) 2 [13][14][15][16][17][18][19][20] or Mg((CF 3 SO 2 ) 2 N) 2 (Mg bis (trifluoromethylsulfonyl)imide, MgTFSI 2 ) [20][21][22][23][24][25][26][27] have been found to support largely reversible Mg plating and stripping without negative impact on the cell components (such as corrosion, which poses a problem in Cl-containing electrolytes). [4] However, even for these electrolytes, the oxidative instability of the borohydride, [6] as well as the Mg 2 + - [18,28] and moistureinduced [16,25,29,30] decomposition of TFSI À , severely limit their application.…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, Mg 2+ ions weakly bound by [TFSA] − in Mg(TFSA) 2 /triglyme electrolyte undergo slow reduction decomposition, allowing Mg to deposit on the anode. [ 32 ]…”
Section: Mg Anodesmentioning
confidence: 99%
“…This high oxidation stability was also observed in other studies, but was not explained satisfactorily. [ 17c,32,51,57 ] Combined with S/CMK‐3 cathodes, the resulting Mg–S batteries displayed a reversible discharge capacity of ≈200 mA h g −1 after 100 cycles. [ 51 ]…”
Section: Electrolytesmentioning
confidence: 99%
“…[21][22][23][24] However, the interfacial instability of [TFSA] À moderates cycling efficiency and causes high interfacial resistance with magnesium anodes. 25,26 In contrast, weakly coordinated anion-based electrolytes incorporating boron-cluster, fluorinated alkoxyborate, and fluorinated alkoxyaluminate anions are a promising option for fulfilling the MB operation requirements. [27][28][29][30][31][32][33][34][35] Owing to their favorable electrochemical properties and structures those are easily modified by simple synthesis methods, fluorinated alkoxyborate and alkoxyaluminate electrolytes have attracted the attention and fascination of many researchers, and various related materials including calcium and zinc salts have also been developed.…”
Section: Introductionmentioning
confidence: 99%